Uji Cemaran Mikroba dan Kapang Khamir Ekstrak Air Daun Muntingia calabura L. (Kersen) - Aulia Nur Rahmawati; Dwi Saryanti; Fryda Nurita Sari; Irma Yovita Turnip (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Kersen (Mutingia calabura L.) is a plant that can be used as a raw material for medicine because it has many medicinal benefits. Kersen as a medicinal raw material must pass a quality parameter testing process to be safe to use. One of the extract quality parameters is the total plate count for microbial (ALT) and yeast contamination (AKK). This study aims to evaluate the suitability of microbial and yeast contamination in the water extract of Kersen leaves to the applicable regulations. Extraction of Kersen leaves used maceration method with water solvent for 3 days with a ratio of 1:10. The results obtained from the water extract of Kersen leaves are organoleptically in the form of thick extract, dark brown in color, sour taste, bitter, and has a distinctive odor. The ALT value in the aqueous extract of cherry leaves was 8.4 x 10⁴ colonies/g. The AKK value in the aqueous extract of cherry leaves was 102 colonies/g which was reported as an approximate AKK value. The ALT and AKK values in the water extract of Kersen leaves meet the safety and quality requirements of traditional medicine.